Study the Content of some Secondary Metabolites in Roots of Glycyrrhiza glabra Gathered from Different Natural Localities in Kerman Province of IRAN - H Oloumi; N Hassibi (Institue of Medicinal Plants, ACECR, 2012)
Background: Glycyrrhiza glabra roots and rhizomes which are extensively used in herbal medicines for them health effects containing more than 100 various useful compounds including phenolics and triterpene saponins (glycyrrizin) grow as a weedy plants in many different localities of Kerman province.   Objective: Regards to application of licorice roots in pharmaceutical industry, the mail goal was the comparison of some biochemical compounds content important in pharmacy, food industry and economics in G. glabra root gathering from seven localities of Kerman province.   Methods: In this research project, the content of total phenolic compounds, flavonoids and other UV absorbent compounds, tannins, anthocyanins and glycyrrhizin gathered from some natural localities of Kerman province including Baft, Bardsir, Rayen, Zangiabad and Koohbanan was investigated.   Results: The highest content of glycyrrhizin was found in Andohjerd. Shahrbabak locality showed the highest content of total phenolic compounds while the lowest was found in Andohjerd. Tannins content were highest in roots gathered from Baft. Conclusion: Based on the results, in seems that the profile of secondary metabolites differs depending on climate parameters and environmental conditions. Therefore, roots gathered from Andohjerd with lowest height show higher quality of regards to glycyrrhizin production and roots form localities with more height like Rayen and Baft have more total phenolic compounds.